A detailed insight into drug delivery from PEDOT based on analytical methods: Effects and side effects. Issue 3 (28th July 2014) - Boehler, Christian; Asplund, Maria
Abstract The possibility to release drugs from conducting polymers, like polypyrrole or poly(3, 4‐ethylenedioxythiophene) (PEDOT), has been described and investigated for a variety of different substances during the last years, showing a wide interest in these release systems. A point that has not been looked at so far however is the possibility of other substances, next to the intended ones, leaving the polymer film under the high voltage excursions during redox sweeping. In this study we target this weakness of commonly used detection methods by implementing a high precision analytical method (high‐performance liquid chromatography) that allows a separation and subsequently a detailed quantification of all possible release products. We could identify a significantly more complex release behavior for a PEDOT:Dex system than has been assumed so far, revealing the active release of the monomer upon redox activation. The released EDOT could thereby be shown to result from the bulk material, causing a considerable loss of polymer (>10% during six release events) that could partly account for the observed degradation or delamination effects of drug‐eluting coatings. The monomer leakage was found to be substantially higher for a PEDOT:Dex film compared to a PEDOT:PSS sample. This finding indicates an overestimation of drug release if side products are mistaken for the actual drug mass. Moreover the full picture of released substances implements the need for further studies to reduce the monomer leakage and identify possible adverse effects, especially in the perspective of releasing an anti‐inflammatory substance for attenuation of the foreign body reaction toward implanted electrodes. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 1200–1207, 2015.